From the Battlefield to the Bedside: Supporting Warfighter and Civilian Health With the "ART" of Whole Genome Sequencing for Antibiotic Resistance and Outbreak Investigations. Issue 7 (1st July 2016) - Lesho, Emil; Lin, Xiaoxu; Clifford, Robert; Snesrud, Erik; Onmus-Leone, Fatma; Appalla, Lakshmi; Ong, Ana; Maybank, Rosslyn; Nielsen, Lindsey; Kwak, Yoon; Hinkle, Mary; Turco, John; et al.
ABSTRACT: Awareness, responsiveness, and throughput characterize an approach for enhancing the clinical impact of whole genome sequencing for austere environments and for large geographically dispersed health systems. This Department of Defense approach is informing interagency efforts linking antibiograms of multidrug-resistant organisms to their genome sequences in a public database.